New material of Sus strozzii (Suidae, Mammalia) from the Early Pleistocene of Italy and a phylogenetic analysis of suines. (15th August 2018) - Cherin, Marco; Sorbelli, Leonardo; Crotti, Marco; Iurino, Dawid A.; Sardella, Raffaele; Souron, Antoine
Abstract: Sus strozzii is the only species of Suinae occurring in the first part of Early Pleistocene in Europe and western Asia. It is characterized by a large body size and several morphological similarities with extinct and extant pigs from Island South East Asia (ISEA), such as the Javan Warty Pig S. verrucosus . In this study, a new mandible of S. strozzii from the Early Pleistocene of Pantalla (central Italy) is described and the diagnosis of the species is emended. Based on 52 craniomandibular and dental morphological characters, the first phylogenetic analysis of both living and fossil Eurasian and African Suinae is carried out to reconstruct their relationships. Our results are in agreement with the literature based on molecular and/or morphological analyses. The late Miocene Microstonyx is the first taxon to branch off the monophyletic Suinae clade. The separation between the African ( Kolpochoerus / Hylochoerus and Metridiochoerus / Phacochoerus ) and the Eurasian ( Sus ) clades occurred early, probably even in the late Miocene. The inclusion of Potamochoerus in the latter group is questionable, being probably due to the retaining of similar plesiomorphic characters in this African pig and in Sus . The Wild Boar S. scrofa and the Early–Middle Pleistocene S. lydekkeri are the species of Sus that display the most numerous plesiomorphic character states. They are followed by the monophyletic group of suines that show verrucosic lower canines, which includes the Pliocene S. arvernensis, S. strozzii, and the extinct and extant verrucosic pigs from ISEA. Highlights: We describe a Suinae mandible from central Italy (Late Villafranchian). We refer the specimen to the large-sized suine Sus strozzii. Sus strozzii shares many similarities with pigs from Island South East Asia (ISEA). We offer the first cladistic morphological analysis of extinct/extant Old World Suinae. Phylogenetic relationships between S. strozzii, S. arvernensis and ISEA pigs are close.